The structure of egg batches, number of eggs and egg hatching rates of pine processionary moth Thaumetopoea pityocampa (Denis & Schiffermüller, 1775) / Thaumetopoea wilkinsoni Tams, 1924 (Lepidoptera: Notodontidae) - Cansu Keleş; Saliha Voyvot; Ertuğrul Bilgili (Doğal Afetler ve Çevre Dergisi)
Pine processionary moth (Thaumetopoea pityocampa (Den. & Schiff.) / Thaumetopoea wilkinsoni (Tams)) is an oligofag defoliator in pine forests. In this study, the structure of egg batches, number of eggs, egg-laying patterns and egg hatching rates of the insect were investigated. A total of 841 egg-batches were collected from different calabrian pine [Pinus brutia (Tenore)] forests located in 11 provinces in Turkey. The average number of eggs in these sites was 194,7, the average rate of hatching was 63,7%. The average number of eggs at the low, middle and high elevations were found to be 183,7, 197,8 and 214,6; and the rate of hatching were 60,1%, 67,6% and 71,9%, respectively. The average number of eggs collected in lower, middle and upper parts of tree crowns were 185,8, 167,0 and 201,7 (mean=184,8); and the rate of hatching was 67,0%, 64,7% and 69,3% (mean=66,9%), respectively. Results indicated small differences in the number of eggs and hatching rate in relation to the position in crown and elevation, however, except for the distance to needle sheath in relation to elevation, the differences were not statistically significant at 95% significance level (p<0.05).